P585 Efficacy of iDose dashboard forecast for individualising Infliximab therapy: an Indian experience. (25th January 2019) - Dave, M; Dherai, A; Desai, D; Mould, D; Ashavaid, T
Abstract: Background: Infliximab (IFX), a monoclonal antibody, is widely used in Inflammatory bowel disease (IBD) refractory to conventional immunosuppressive agents. Standard of care dosing of IFX in IBD is associated with significant loss of response, both primary and secondary. The loss of response is attributed to its highly variable and complex pharmacokinetics affecting IFX clearance. Dashboards based on Bayesian algorithms using multi-variate determinants of IFX concentration are proposed for individualised dosing. We aimed to assess the accuracy and efficacy of the iDose dashboard system. Methods: The IFX levels estimated in our laboratory in IBD patients as a part of clinical service from April 2016 to October 2018 were compared with that forecasted by the iDose dashboard software. A total of 41 data points (estimated IFX level) were available from 29 patients. Patient's clinical history, demographic details, laboratory findings such as albumin and CRP were entered in the software and the predicted IFX level was compared with the estimated level. In addition, dashboard guided dosing strategy was prescribed in 5 patients who did not respond to standard dosing schedule and the clinical outcome was followed. Results: Of 41 (73%) data points, 30 showed concordance in IFX level. An iDose guided dosing was clinically useful to achieve target IFX level and therapeutic response in 4/5 patients. The dosing interval was increased from 4 weeks to 7 weeks in one patients (with cost saving); in 3 patients the dosing was optimised with multiple drug estimations and iDose prediction with clinical remission and reduction in fistula output. One patient was switched to adalimumab due development of antibodies Conclusions: There was 73% concurrence between the iDose dashboard predicted and observed infliximab level. This approach optimised the infliximab therapy by individualised IFX dosing and duration. It has potential to save cost.